Utilization of Various Organic Mulches in Maintaining Soil Moisture in Oil Palm (Elaeis guineensis J.) Main-Nursery During Dry Season - Widiyani, Dimas Prakoswo; Sari, Resti Puspa Kartika; Airlangga, Tandaditya Ariefandra (Biotropika: Journal of Tropical Biology, 2025)
One of the determinants of the success of an oil palm cultivation business is the provision of quality seeds. Seedlings can be produced through good maintenance. Oil palm nurseries are divided into two stages: the pre-nursery phase lasts 3 months after germination, and the main-nursery phase lasts  7-9 months after pre-nursery. In uncertain weather like today, it is very difficult to predict environmental conditions that are suitable for oil palm seedlings. Meanwhile, in the main nursery phase, the seeds are placed in an open area with adjusted planting distances. One alternative to reduce evaporation and save water is by providing several types of organic mulch. This research aims to determine the effectiveness of using various types of organic mulch in enhancing the growth of oil palm plants in the main nursery during the dry season. This research used a randomised block design with four treatments, including no mulch (control), empty palm fruit bunch mulch, straw, and reed. Each treatment uses a weight of 50 grams of mulch per plant in a polybag. Based on the results and discussion, it was found that using organic mulch could increase plant height, number of leaves, stem diameter, soil moisture and soil organic C content. However, the use of mulch does not affect soil pH.